2013
DOI: 10.1111/adj.12047
|View full text |Cite
|
Sign up to set email alerts
|

The application of caries risk assessment in minimum intervention dentistry

Abstract: Caries risk assessment forms the cornerstone for the successful application of a minimum intervention dentistry philosophy in the management of dental caries. Patients, particularly those with evidence of active dental caries at baseline, require a caries risk assessment to identify those risk factors that will most likely contribute to the progression of the carious disease process. Once identified, these factors should be eliminated or at least moderated to ensure the disease progression is stabilized before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 57 publications
1
26
0
5
Order By: Relevance
“…[13][14][15] However, most of these caries prediction attempts are not noninvasive but minimally invasive and individual level studies. 13,20 The caries prediction model that was generated from our preliminary study is a totally noninvasive population level study as reported by others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[13][14][15] However, most of these caries prediction attempts are not noninvasive but minimally invasive and individual level studies. 13,20 The caries prediction model that was generated from our preliminary study is a totally noninvasive population level study as reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, most of these caries prediction attempts are not noninvasive but minimally invasive and individual level studies. 13,20 The caries prediction model that was generated from our preliminary study is a totally noninvasive population level study as reported by others. 14,15 Further, several recent reviews 13,21 have highlighted the importance of having minimally invasive dentistry caries management strategies that should be incorporated to estimate caries activity at each visit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations